The Socioeconomic Incorporation of Immigrant and Native‐born Day Labourers in Tshwane, South Africa. (27th December 2016) - Theodore, Nik; Blaauw, Derick; Pretorius, Anmar; Schenck, Catherina
Abstract: It has been widely documented that unauthorized immigrants experience adverse economic incorporation in destination countries, particularly in the global North. Faced with restricted employment opportunities, many are drawn into informalizing segments of the labour market where earnings are low and unstable. Much less is known about how immigrant workers fare in the informal economy of cities of the South. Using surveys conducted in 2004, 2007 and 2015, we examine the economic outcomes of immigrant and native‐born workers who participate in the day labour markets of Tshwane, South Africa. In 2004 there were signs that foreign‐born workers enjoyed modestly better outcomes than South Africa‐born workers. In the latter periods, however, these advantages have disappeared and there are indications of a downward convergence of employment outcomes. The article concludes with a call for creating worker centres to regulate informal job markets for the benefit of workers, regardless of immigration status.